Электронный корпус как основа словарей современного английского языка. Электронды корпус заманауи ағылшын сөздіктерінің негізі ретінде. (Eurasian Journal of Philology Science and Education, 2015)
Electronic corpora as a basis of modern English dictionariesThe article is devoted to analysis of the various aspects of correlation between two linguistic disciplines: corpus linguistics and lexicography. It describes the current state of electronic corpora, provides a brief overview of the development stages of English lexicography. The article details the process of compiling major English corpora and defines their main functions. Particular attention is paid to determine the value of electronic corpora when creating dictionaries, the positive and negative impact of corpora on the development of lexicography.
Keywords: electronic corpus; lexicography; corpus linguistics; text; dictionary